Fabricate and investigate the performance of the flow-through solar evacuated tube using water-based nanofluids - Norazreen, Samsuri (2012)
Experiments are undertaken to determine the efficiency of Evacuated Tube Collector (ETC) using water based Titanium Oxide (Ti02) nanofluid at Pekan campus (3˚30’ N, 103˚ 25’ E) Faculty of Mechanical Engineering, University Malaysia Pahang for conversion of solar thermal energy. These projects are carried out to fabricate the bracket for Evacuated Tube Collector (ETC), to determine the best parameter and to compare the efficiency of water and Ti02. Malaysia lies in the equatorial zone with an average daily solar insolation of more than 900W/m2 and can reach a maximum of 1200 W/m2 for most of the year. Nanofluids are liquids in which nanosize particles of metal or their oxides are dispersed in a base liquid such as water. It results in higher values of thermal conductivity compared to the base fluid. The increase in thermal conductivity with temperature is advantageous for applications in collectors, as the solar insolation varies throughout the day, with a minimum in the morning reaching a maximum at about 2pm and reducing thereafter. The fabrication of bracket was done by using two hydraulic car jacks. The best parameter for ETC is verified by flow rate for water is 2.7L/min and the tilt angle throughout the year is 8.20. The increment by temperature different in ETC is 23.46% maximum with 0.3vt% for 30-50nm size Ti02 nanoparticles dispersed in water, compared to the system working with water. However, the efficiency of solar ETC increased with increment in concentration from 0.3vt% and distilled water is 25.89% when the flow rate is fixed at 2.7 LPM. Thus, the nanofluids is capable to absorb solar thermal energy at all available solar insolations in the present experiment.